2010
DOI: 10.1021/tx100131f
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Glutathione S-Transferases in the Inactivation of Reactive Metabolites of Clozapine

Abstract: The conjugation of reactive drug metabolites to GSH is considered an important detoxification mechanism that can be spontaneous and/or mediated by glutathione S-transferases (GSTs). In case GSTs play an important role in GSH conjugation, genetically determined deficiencies in GSTs may be a risk factor for adverse drug reactions (ADRs) resulting from reactive drug metabolites. So far, the role of GSTs in the detoxification of reactive intermediates of clozapine, a drug-causing idiosyncratic drug reactions (IDRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
104
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 34 publications
8
104
2
Order By: Relevance
“…Three of the four tested hGSTs showed strongly increased total GSH conjugation and also resulted in formation of different regioisomeric GSH conjugates of CLZ ( Fig. 1) (Dragovic et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Three of the four tested hGSTs showed strongly increased total GSH conjugation and also resulted in formation of different regioisomeric GSH conjugates of CLZ ( Fig. 1) (Dragovic et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…However, we recently demonstrated that these GSH conjugates, CG-5 and CG-6 in Fig. 1, are formed at high levels when CLZ incubations with purified CYP102A1 M11H and human liver microsomes were supplemented with human glutathione transferases (hGSTs) (Dragovic et al, 2010). Three of the four tested hGSTs showed strongly increased total GSH conjugation and also resulted in formation of different regioisomeric GSH conjugates of CLZ ( Fig.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations